Metabolic Profiling, Antioxidant, and Anti-lipase Activity from Combined Leaves Extracts of Tamarindus indica and Murraya paniculata: A Simplex Lattice Design Approach - Sholikhah, Eti Nurwening; Wiyono, Tri; Pratiwi, Woro Rukmi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Tamarindus indica leaves are recognized for their potent antioxidant and hypolipidemic properties, whereas Murraya paniculata leaves are known for their abilities to lower lipids and glucose levels. This study aimed to assess the combined extract of both leaves against pancreatic lipase inhibition and analyze their metabolomic profiles as an initial step toward developing a polyherbal treatment for hypertriglyceridemia. The extracts were subjected to Liquid Chromatography-High Resolution Mass Spectrometer (LC-HRMS) untargeted system coupled with Compounds Discoverer software to reveal their metabolomic profile. Subsequently, both individual extracts and their combination were evaluated for anti-lipase activity using pancreatic lipase enzyme with p-nitrophenyl butyrate as the substrate. The combination of the two extracts (0-300 μg/mL, 300 μg/mL in total) was prepared following the Simplex Lattice Experimental Design with 5 different composition variations. Results: The findings indicated that Tamarindus indica leaf extract (TIE) predominantly exhibited lipase inhibitory activity. Interestingly, the addition of Murraya paniculata extract (MPE) diminished this enzyme inhibitory effect. TIE was found to be rich in polyhydroxy flavonoids followed by fatty amides, whereas MPE contained mainly polymethoxy flavonoids, fatty amides, and coumarins. The presence of fatty amides in both extracts was identified as a potential cause for this incompatibility. In summary, Tamarindus indica leaf extract demonstrated strong lipase inhibition; however, its effectiveness was reduced when combined with Murraya paniculata extract, possibly due to primary fatty amides. Further research is necessary to explore strategies for eliminating these compounds and confirming their impact in vivo.